PERAN ADMINISTRASI PERPAJAKAN DALAM MENDORONG PEMBANGUNAN EKONOMI BERKELANJUTAN: STUDI TENTANG IMPLEMENTASI KEBIJAKAN PAJAK DAN DAMPAKNYA PADA SEKTOR EKONOMI STRATEGIS - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2025)
This study examines the strategic role of tax administration in promoting sustainable economic development through the implementation of tax policies and their impact on strategic economic sectors. Using a literature review method, this study analyses how an effective administration system—covering digitalisation, socialisation, data-based law enforcement, and inter-agency synergy—has succeeded in increasing taxpayer compliance and optimising state revenue for financing green infrastructure and inclusive programmes. The results show that fiscal incentives such as tax holidays and carbon taxes stimulate investment, innovation, and environmentally friendly transformation in the manufacturing, mining, and strategic services sectors, although administrative challenges require continuous reform to maximise the multiplier effect for inclusive and sustainable growth.